Performance measure of airline websites using analytical hierarchy process & fuzzy analytical hierarchy process - Dominic, P.D.D. (Institute of Electrical and Electronics Engineers Inc., 2014)
Airline website is the major online channel that attracts the customers around the globe. The quality of the website is the main concern for the users who use it. Website quality depends on many criteria from both user's and service providers perspective. This research aims to measure some quality attributes of airlines websites using various online web diagnostic tools. The analytical hierarchy process (AHP) and fuzzy analytical hierarchy process (FAHP) approaches are used to measure and compare the quality of websites for four airlines that operates very frequently in Malaysia. The results suggest that different factors constitute differently to make each airline website successful. Â© 2014 IEEE.